Hydromagnetic Boundary Layer Analysis of Casson Fluid Flow Over an Inclined Porous Magnetised Surface with Radiation and Convective Boundary Conditions - Aloliga, Golbert; Seini, Ibrahim Yakubu; Musah, Rabiu (Science and Technology: Developments and Applications Vol. 10, 2025)
Casson fluid in a non-Darcian porous medium has significant applications in industry. Casson fluids are a type of non-Newtonian fluid with examples as jelly, tomato sauce, human blood, honey, etc. Due to the numerous engineering applications of non-Newtonian Casson fluids, researchers have invested a lot of time in studying the flow of the fluid. The applications include food processing, photodynamic therapy, nuclear cooling, as well as in biological systems. This chapter presents a comprehensive analysis of the hydromagnetic boundary layer behaviour of a non-Newtonian Casson fluid flowing over an inclined porous surface subjected to a transverse magnetic field, thermal radiation, and convective boundary conditions. The study is motivated by applications in engineering fields such as polymer processing, metallurgical operations, and thermal management systems, where control over heat and mass transfer is crucial. The governing partial differential equations, representing the conservation of mass, momentum, energy, and species concentration, are transformed into a set of nonlinear ordinary differential equations using similarity transformations. These equations are then solved numerically to investigate the effects of various physical parameters, including magnetic field strength, radiation parameter, convective heat transfer coefficient, and surface permeability, on the velocity, temperature, and concentration profiles. Results indicate that the presence of a magnetic field enhances the thermal boundary layer thickness, leading to an increased rate of heat transfer. Additionally, the induced magnetic field significantly influences the skin friction coefficient, Nusselt number, and Sherwood number, suggesting that magnetic fields can be effectively utilised to control flow characteristics and enhance thermal performance. The findings of this study provide valuable insights into the manipulation of flow and heat transfer in non-Newtonian fluids under combined physical effects, offering guidance for the design and optimisation of industrial processes involving Casson fluids.